Memória e patrimônio : os símbolos esquecidos no cemitério municipal de Soledade (1871-1935) - Pereira, Magda da Silva (2009)
This thesis aims at carrying out research on the historical significance that cemeteries are for the memory of a community, with the theme: Memory and Heritage: the forgotten symbols at the municipal cemetery of Soledad, in chronological March 1871 to 1935. Subsidies of this research was collected through informal interviews, literature reviews, archival research and photographic survey, in order to see how the cemetery can serve as a historical source on cultural, social and economic aspects of a community. The dissertation is divided into four chapters, which takes place a discussion of death in the history of churches and holy fields, and specifically, the municipal cemetery of the existent and Soledad in their graves. The cemeteries appear as a form of reproduction of memory through their art, their epitaphs, its architecture, among other things. It is an inherent part in preserving local history, preserving the cultural identity of a community, highlighting the religious, ideological, artistic presence, the ethnic and the local economic context and the periods of rise and decline of every day, all through symbolic representation contained in the tombs of the cemeteries